Analysis of Lampung Marine Tourism Contents on Social Media - Wijaya, Toni; Hartoyo; Wardani, Andy Cory (Technium Social Sciences Journal, 2026)
Marine tourism in Lampung province has significantly contributed to its development. In fact, it can be said that the majority of tourists visiting Lampung visit marine tourism attractions. The rapid growth of social media has resulted in many social media accounts focusing on tourism news. In this study, the Instagram accounts examined were @lampuung and @potraitlampung. These two accounts were selected based on their popularity, followers, and engagement. The results showed that @potraitlampung posted more marine tourism content than @lampuung. In terms of content, there are differences in posting styles, indicating distinct characteristics between the two accounts.